AB1049 Musculoskeletal Manifestations in Renal Hemodialysis Patients. (15th July 2016) - Gheita, T.A.; Sayed, S.; Al-ghitany, A.; Ezzat, H.
Abstract : Background: Pain is a significant problem in more than 50% of hemodialysis patients and is not being effectively managed 1 . In patients on regular dialysis, musculoskeletal pain was identified as the most disturbing pain and the majority reported that pain limited their daily life activities 2 Objectives: The aim of the study is to detect and describe the incidence of musculoskeletal manifestations, comorbidities and gender differences in renal failure patients on regular hemodialysis Methods: Forty-nine patients with renal failure and on regular dialysis were included in the present study. The patients were subjected to full history taking and clinical examination. Blood samples were collected before the mid-week session for laboratory investigations. The bone mineral density (BMD) was assessed by dual energy X-ray absorptiometry (DXA) in all patients. Kt/V was used as a marker of dialysis adequacy Results: The 49 patients mean age was 54.41±15.9 years. They were 28 males and 21 females. The dialysis duration was 3±2.31 years. Comorbidities were present as diabetes (45%), hypertension (96%), cardiovascular (33%), cerebrovascular stroke (6%), hyperuricemia (37%), hepatitis C (16%) and amyloidosis (8%). The following musculoskeletal findings were present in descending frequency: fibromyalgia syndrome (51%), myalgias (37%), arthralgia (37%), flexor tenosynovitis (29%), cramps (29%), ectopic calcifications (25%), flexion deformity of the elbow (16%), carpal tunnel syndrome (14%), and destructive spondyloarthritis (8%). Vasculitis was present in 2. Positive anti-CCP was present in 1 female and rheumatoid factor in 4 females and 1 male. Otherwise, there was a tendency to a higher frequency of musculoskeletal findings in males. Vitamin D insufficiency (25.1±14.6ng/ml) and reduced bone mineral density were present. The DXA t-score at lumbosacral spine was -1.51±1.77, hip (-1.65±1.59) and forearm (-1.89±1.9). Conclusions: Musculoskeletal manifestations and comorbidities are frequent and overlooked in hemodialysis patients especially males and the associated chronic pain may affect their quality of life. References: Davison SN. Pain in hemodialysis patients: prevalence, cause, severity, and management. Am J Kidney Dis. 2003;42(6):1239–47. Gamondi C, Galli N, Schönholzer C, Marone C, Zwahlen H, Gabutti L, et al. Frequency and severity of pain and symptom distress among patients with chronic kidney disease receiving dialysis. Swiss Med Wkly. 2013;143:w13750 Disclosure of Interest: None declared